Estudo das características clínico-epidemiológicas da infecção pulmonar em pacientes transplantados renais submetidos à broncoscopia ou à biópsia sob visualização direta - Carvalhaes, Cecilia Helena Vieira Franco de Godoy [UNIFESP] (2008)
Purposes: To describe clinical and epidemiological aspects of pulmonary infection in kidney transplant recipients who underwent transbronchial biopsy or open lung biopsy. To measure the impact of invasive diagnosis on antimicrobial therapy, diagnosis accuracy and procedures related complications. Methods: Retrospective review of pulmonary infection in kidney transplant recipients who underwent pulmonary transbronchial biopsy (TBB) or open lung biopsy (OLB) during the period of 2000-2005 at Hospital do Rim e Hipertensão and Hospital São Paulo, both affiliated to Federal University of Sao Paulo. Recipients of kidney transplant who underwent lung biopsy for pneumonia investigation were identified from the Pathology Service’s database. Clinical and radiology aspects, such as time of presentation, immunessupressant regimen and antimicrobial empiric therapy were analyzed. Invasive methodology was evaluated regarding accuracy, impact on antimicrobial therapy and procedure related complication. Results: One hundred and ten patients were included, 104 underwent TBB, 18 underwent TBB followed by OLB and 6 underwent only OLB. The most frequent pathogens were bacterial agents with a 26.4% occurrence (including Legionella pneumophila and Nocardia spp), followed by 18.2% Mycobacterium tuberculosis, 10.9% fungi (Criptococcus neoformans, P. jiroveci and Histoplasma capsulatum) and 4.5% CMV. Clinical and radiological presentations were variable. High resolution computed tomography weas performed in 68 patients and showed additional information in 51,5% of the cases. The TBB accuracy was 58.4%, antimicrobial therapy was modified in 29.6% patients and procedure complication occurred in 28.8%. The OLB procedure results were 87.5%, 76.5% and 16.7%, respectively. The overall mortality was 16.4% and there were no deaths related to any invasive procedure. Conclusions: The variable clinical and radiological variety presentation makes etiological determination and empiric antimicrobial therapy hard to define. High resolution computed tomography is a helpful tool not only in diagnosis but also as a guide to invasive methods for diagnosis. TBB and OLB had impact on determining 11.8% of non-suspected diagnosis. Open lung biopsy showed greater impact (37.5%) on antimicrobial therapy modification than the transbronchial biopsy (18.3%), as either better accuracy without procedure related complications that limited its use.